Bioengineered wound and burn healing substitutes: Novel design for biomedical applications and general aspects - (:unkn) unknown (CABI International, 2016)
Wound healing is the inherent ability of an organism to protect itself against injuries. Cumulative evidence indicates that the healing process patterns in part embryonic morphogenesis and may result in either organ regeneration or scarring, phenomena that are developmental stage- or age-dependent. Tissue regeneration by using biomaterials and skin grafting materials in periapical surgery is an example of tissue engineering technology. Significant progress has been made in the development of in vitro-engineered skin substitutes that mimic human skin, either to be used for the replacement of lost skin or for the establishment of in vitro skin research models. Full-thickness skin deficits are indications to autologic skin graft. In extensive skin injuries an employment of skin substitutes is sometimes necessary. This review presents the classification of skin substitutes (permanent, temporary, biological, synthetic). The different kinds of skin substitutes approved for commercial production are described (epidermal substitutes, dermal substitutes, composite dermo-epidermal substitutes). The possibilities of clinical applications of skin equivalents and results obtained by many authors after employment of artificial skin are also presented. Important new discoveries in key elements of engineering of tissue-engineered skin including cell sources, biomaterials and growth factors, etc., are summarized. Basic and clinical applications for engineered skin substitutes in cell therapy, tissue engineering and biomedical research continue to drive design improvements premised on these structure- and function-based engineering paradigms. © CAB International 2017. All rights reserved.